Association between previous rheumatoid arthritis and COVID-19 and its severity: a nationwide cohort study in South Korea - Hyo Geun Choi; Younghee Jung; Mihye Kwon (BMJ Open)
Objectives The prevalence of rheumatoid arthritis (RA) among patients with COVID-19 and the association between RA and the outcome of COVID-19 remain unclear. We aimed to compare the prevalence of RA between participants with and without COVID-19; we then analysed the association between the presence of RA and the severity of COVID-19.Design A cross-sectional study.Setting Data from a nationwide COVID-19 cohort database by the Korea National Health Insurance Corporation were used.Participants and interventions A total of 8070 patients with COVID-19 (1 January 2020 through 4 June 2020) were matched with 32 280 control participants with regard to age, sex and income. Patients with COVID-19 were confirmed by SARS-CoV-2 PCR and controls were collected from the database. RA was confirmed using the diagnostic code (International Classification of Disease, Tenth Revision) and medication claim codes. Conditional/unconditional logistic regression was applied to analyse the association between RA and COVID-19.Primary outcome and secondary outcome Laboratory confirmation of SARS-CoV-2 infection was defined as the primary outcome. The secondary outcome was severe COVID-19 defined as a history of intensive care unit admission, invasive ventilation or death.Results The prevalence of RA in the COVID-19 (0.4%, 35/8070) and control (0.4%, 121/32,280) groups did not differ (p=0.446). After adjusting for underlying diseases, no association between RA and COVID-19 was observed (adjusted OR=1.14, 95% CI: 0.78 to 1.67) and COVID-19 severity was not associated with RA (adjusted OR=0.62, 95% CI: 0.14 to 7.29). The overall mortality rate was 2.9% (237/8070) and RA was not significantly associated with mortality (adjusted OR=1.64, 95% CI: 0.33 to 8.15).Conclusion We did not find an association between the presence of RA and COVID-19. In addition, RA was not associated with the severity of COVID-19.